2023
DOI: 10.1038/s41746-023-00884-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose variance measured by continuous glucose monitors across the menstrual cycle

Abstract: Past studies on how blood glucose levels vary across the menstrual cycle have largely shown inconsistent results based on limited blood draws. In this study, 49 individuals wore a Dexcom G6 continuous glucose monitor and a Fitbit Sense smartwatch while measuring their menstrual hormones and self-reporting characteristics of their menstrual cycles daily. The average duration of participation was 79.3 ± 21.2 days, leading to a total of 149 cycles and 554 phases in our dataset. We use periodic restricted cubic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Lin et al addressed the issue of limited blood sampling time points by analyzing glucose variance in the course of the menstrual cycle using continuous glucose measurement. While not performing an OGTT, their results support the findings of Jarrett and Graver, Peppler et al, and Brennan et al, as they found that glucose values were the lowest during late FP, increased during ovulation, and peaked in the LP phase 75 .…”
Section: Introductionsupporting
confidence: 78%
“…Lin et al addressed the issue of limited blood sampling time points by analyzing glucose variance in the course of the menstrual cycle using continuous glucose measurement. While not performing an OGTT, their results support the findings of Jarrett and Graver, Peppler et al, and Brennan et al, as they found that glucose values were the lowest during late FP, increased during ovulation, and peaked in the LP phase 75 .…”
Section: Introductionsupporting
confidence: 78%
“…The precise mechanism behind catamenial hyperglycemia remains uncertain, but it is likely associated with decreased insulin sensitivity caused by elevated levels of circulating progesterone. Basic research in rats has indicated that progesterone can reduce glucose uptake in skeletal and adipose tissues ( 17 ). According to the findings of Cawood et al., approximately 67% of women with diabetes encountered fluctuations in their blood glucose levels during the premenstrual period ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…While the menstrual cycle lasts ~28 days, the estrous cycle is shorter, lasting 4–5 days ( Ajayi & Akhigbe 2020 , Gutierrez-Castellanos et al 2022 ). Blood glucose concentrations have been found to change throughout the menstrual cycle ( Lin et al 2023 ). It could be argued that the estrous cycle increases variance of metabolic studies; therefore, data from female rodents should be presented by estrous phase ( Della Torre et al 2016 ).…”
Section: Factors To Consider When Assessing Glucose Metabolism ...mentioning
confidence: 99%